Investigations of power quality disturbances in a variable speed parallel pumping system with grid tied solar PV - Shankar V.K.A.; Umashankar S.; Sanjeevikumar P.; Viliam F.; Ramachandaramurthy V.K.; Mihet-Popa L. (Elsevier Ltd, 2023)
Centrifugal pumps; Electric fault currents; Energy utilization; Power quality; Pumps; Variable speed drives; Water supply; Water supply systems; Affinity laws; Control techniques; Electricity-consumption; Loading condition; Mitigation techniques; Parallel pumping systems; Point of common coupling; Power quality disturbances; Electric power transmission networks